Bandgap engineering in TiO2/rGO 1D photonic metasurfaces as broadband solar absorber - Saurabh Y.K.; Jha P.A.; Dubey P.K.; Jha P.K.; Singh P. (My University, 2025)
Inability to use full solar energy, especially near infrared radiation (NIR: 780-1400 nm), is one of the major limitations for solar energy harvesting due to the narrow bandgap (electronic as well as photonic). In this work, we designed the 1D photonic metasurfaces of TiO 2 with reduced graphene oxide (rGO) in an attempt to obtain broader absorption bandwidth in NIR. Further, to realize this experimentally, graphene oxide reduced TiO 2 nanocomposites are synthesized using the hydrothermal method to form a quantum well. The composites are observed in the anatase phase of TiO 2 with graphitic reflection, and microstructural studies that indicate the conversion of TiO 2 nanoparticles into nanotubes with reduced graphene oxide intercalation forming a kind of self-assembled metasurfaces. UV-vis absorption studies indicate a significant reduction in bandgap energy; typically, the indirect bandgap reduces near to zero. The experimental and numerical simulation results suggest phonon scattering dominated free carrier absorption in NIR in the TiO 2/rGO metasurface leading to wide broadband absorption (700-10 000 nm). © 2022 Author(s).